2020
DOI: 10.1093/ntr/ntaa196
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Reasons for Using Electronic Cigarettes and Product Characteristics: Findings From the 2018 ITC Four Country Smoking and Vaping Survey

Abstract: Introduction Little is known about why males are more likely to use electronic cigarettes (ECs) compared to females. This study examined gender differences in reasons for vaping and characteristics of EC used (device type, device capacity, e-liquid nicotine strength, and flavour). Methods Data from 3938 current adult (18+ years) at-least-weekly EC users who participated in Wave 2 (2018) ITC Four Country Smoking and Vaping Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…About 50% of respondents believed that e-cigarettes contained less nicotine than conventional cigarettes and intended to use e-cigarettes to assist in quitting smoking. This finding is consistent with previous studies 16 25 26. Earlier studies in Qatar25 and Thailand16 26 found that fewer e-cigarette users believed in the health harm caused by e-cigarettes than non-users 16 25–27…”
Section: Resultssupporting
confidence: 91%
“…About 50% of respondents believed that e-cigarettes contained less nicotine than conventional cigarettes and intended to use e-cigarettes to assist in quitting smoking. This finding is consistent with previous studies 16 25 26. Earlier studies in Qatar25 and Thailand16 26 found that fewer e-cigarette users believed in the health harm caused by e-cigarettes than non-users 16 25–27…”
Section: Resultssupporting
confidence: 91%
“…Our results comport with previous research showing males to be more likely to vape, and use ENDS devices. 34 Results also align with previous research linking the prevalence of dripping with other tobacco-product use. 16 However, our findings on race and ethnicity depart from previous findings on health-risk behaviors among young adults.…”
Section: Discussionsupporting
confidence: 86%
“…We compared the reasons for current smokers using HTPs in Japan with a recent ITC study of the reasons for current smokers using nicotine vaping products (NVPs; e.g., e-cigarettes) in the 2018 ITC Four Country Smoking and Vaping Survey, conducted in the United States, Canada, England, and Australia [30]. Some of the most common reasons for using NVPs were similar to the reasons for current smokers using HTPs in the present study, including the belief that NVPs were "less harmful to me": 74.3% among male and 74.5% among female concurrent smokers compared to 88% of current HTP-cigarette dual users in Japan, and that vaping was less harmful to others: 69.8% among male and 77.8% among female concurrent NVP-cigarette users compared to 83.8% among concurrent HTP-cigarette users in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the presence of strong and enforced smoke-free laws in those four countries, which would highlight the perceived benefits of vaping, relative to the weak and weakly enforced smoke-free laws in Japan [31]. Second, concurrent NVP-cigarette users were much more likely to cite saving money as a reason for using NVPs (64.7% among males, 64.9% among females) vs. concurrent HTP-cigarette users in Japan (20.3%), reflecting both the relatively lower cost of vaping vs. smoking in the four countries and the nearly equal cost of using HTPs vs. smoking in Japan and elsewhere [30], and the overall marketing and positioning of HTPs as a high-end product [28,32].…”
Section: Discussionmentioning
confidence: 99%